Analisis Faktor-Faktor yang Mempengaruhi Kinerja System Informasi Akuntansi - Nakita Sisilia; Rayyan Firdaus (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research discusses the factors that influence the performance of Accounting Information Systems (AIS) in companies, which are very important in supporting operational efficiency and decision making. This system plays a vital role in managing financial data, but is often hampered by problems with the quality of human resources, technology and data management. The theoretical study uses the Information Systems Success Model and Technology Acceptance Model to evaluate AIS performance in terms of system quality, information, services and user acceptance. This research methodology uses a qualitative approach with document analysis, reviewing journals and related research reports. The research results show that the main factors influencing AIS performance include HR skills, choosing the right technology, data quality, and user adaptation to the system. Therefore, companies need to invest in human resource development, choose appropriate technology, and ensure accurate data management. In conclusion, to improve AIS performance, companies must manage these factors well so that they can support more precise and efficient decision making.